Pengaruh Perilaku Keuangan, Kesadaran Keuangan, Pengetahuan Keuangan Dan Sikap Keuangan Terhadap Kinerja UMKM Di Kecamatan Samudera Kabupaten Aceh Utara - Zawi, Muhammad Boy; ., Chairil Akhyar; Marzuki, Marzuki Marzuki (Jurnal Visioner & Strategis, 2024)
This research aims to analyze the influence of financial behavior, financial awareness, financial knowledge and financial attitudes on the performance of MSMEs in Samudera District, North Aceh Regency. The sample in this research was 69 MSMEs in Samudera District, North Aceh Regency and used the Slovin technique. The analytical tool used is multiple linear regression. The results of the research show that the variables financial behavior, financial awareness, financial knowledge and financial attitudes have a significant positive effect on the performance of MSMEs both partially and simultaneously. Keywords: financial behavior, financial awareness, financial knowledge, financial attitude, MSME performance